Fighting standards with standards: harmonization, rents, and social accountability in certified agrofood networks - Mutersbaugh, Tad (Environment & Planning A, 2005)
In this paper I explore the remaking of globalized standards through harmonization, and its impact upon certified-organic and fair-trade agrofood networks. I focus on certification standards and discuss four shifts associated with globalized standards (an increased importance of multilateral institutions, changes to standards language, displacement of network-specific standards, and a shift away from relational standards). It is then argued, with reference to value-chain rent theory, that the shift to globalized standards has transformed rent relations in ways that benefit certain actors (that is, retailers) and imperil the earnings of others. In brief, globalized standards increase the costs of standards compliance, the full burden of which falls upon immiserated producers, to the point at which farmers see little economic advantage to certified-organic and fair-trade production. I then examine social-accountability standards that seek to `fight standards with standards' by championing the consolidation of strong labor and environmental protections under a single label. The study suggests that a single-label strategy can be successful, yet must struggle to overcome a Polanyian double bind, for, in order to build broad coalitions necessary to extend the reach of protective standards, the coalitions must include corporate interests that prefer weaker, contract-based standards.
Geography
Keywords: agricultural accounting; agricultural industries; applied ecology; environmental policy; retail industry; retail stores

Gramsci, Polanyi and Impressions from Africa on the Social Forum Phenomenon - Bond, Patrick (International Journal of Urban and Regional Research, 2005)
The rise of the Social Forum phenomenon has been heartily welcomed, partly so as to unite diverse discourses of anti-neoliberal and anti-imperialist resistance under a common banner. There are debates worth flagging, however, that draw our attention to political philosophies (typically binary statist versus anti-statist disputes), visions of agency (typically networked movements versus parties), and potentials for revolutionary processes to emerge within ‘civil society’. In the spirit of Polanyi, many South Africans and other Africans are working on ‘decommodification’ strategies that range from particular sites of project-level struggles to national, regional and international advocacy. But we must be conscious, as well, of warnings by Gramsci about the long march through a civil society often co-opted to support state and neoliberal projects. The merits of African intellectual engagements with radical social movements have been shown in sites such as South African cities, but the African Social Forum awaits further opportunities to welcome allied researchers and academics. As the World Social Forum comes to Africa in 2007, Marcuse’s hope that the constituent movements begin to coalesce around a program is timely. However, this is likely to emanate more from intra-sectoral networks rather than from multidisciplinary moments such as the WSF itself. La montée du phénomène des Forums sociaux a été accueillie chaleureusement, en partie comme manière d’unifier sous un même drapeau les multiples discours de la résistance anti-néolibérale et anti-impérialiste. Certains débats éminents attirent pourtant l’attention sur des philosophies politiques (généralement des oppositions binaires étatistes/anti-étatistes), des visions de l’intermédiation (en général, mouvements interconnectés/partis) et des processus révolutionnaires susceptibles de naître au sein de ‘la société civile’. Dans l’esprit de Polanyi, nombre d’Africains, du Sud et d’ailleurs, s’emploient à des stratégies de ‘démarchandisation’ couvrant à la fois sites de conflit particuliers liés à un projet et plaidoyers aux niveaux national, régional et international. Toutefois, il ne faut pas oublier les avertissements de Gramsci pour qui la longue marche passant par la société civile risquait d’être cooptée afin de soutenir des projets gouvernementaux ou néolibéraux. Si les engagements d’intellectuels africains aux côtés de mouvement sociaux radiaux se sont révélés bénéfiques dans des cas tels que les villes d’Afrique du Sud, le Forum social africain espère d’autres occasions de rallier chercheurs et universitaires. Comme le Forum social mondial se tiendra en Afrique en 2007, l’espoir de Marcuse — de voir les mouvements constitutifs s’unir progressivement autour d’un programme — est d’actualité. Cependant, cette évolution viendra plus probablement de réseaux intra-sectoriels que d’élans multidisciplinaires comme le FSM.
Geography; Political Economy
Keywords: GRAMSCI; Antonio; 1891-1937; South Africa; decommodification; development studies; geography; social forum phenomenon

The Global Resistance Reader - Amoore, Louise (Psychology Press, 2005)
The Global Resistance Reader provides the first comprehensive collection of work on the phenomenal rise of transnational social movements and resistance politics: from the visible struggles against the financial, economic and political authority of large international organizations such as the World Trade Organization, World Bank and International Monetary Fund, to the much less visible acts of resistance in everyday life. The conceptual debates, substantive themes and case studies have been selected to open up the idea of global resistance to interrogation and discussion by students and to provide a one-stop orientation for researchers, journalists, policymakers and activists.
Geography; Political Science
Keywords: GILL; Stephen; political science / globalization; political science / reference